Meta Analysis: The Effect of Treffinger Learning Model on Students' Mathematical Creative Thinking Ability - Wahyuningsih, Vebryana; Isnarto, Isnarto; Hendikawati, Putriaji; Mariani, Scolastika; Rosyida, Isnaini (SJME (Supremum Journal of Mathematics Education), 2025)
This study aims to determine the effect of Treffinger learning model on students' mathematical creative thinking ability, based on previous research articles. The method used in this research is meta-analysis. The results of the analysis through the calculation of the t-test and effect size show that , indicating that the average mathematical creative thinking ability of students who use the Treffinger model is higher than the average students who follow conventional learning. Thus, there is a significant influence between the mathematical creative thinking ability of students using the Treffinger model, with an effect size of 1.02, which is classified in the large category.